Starch biosynthesis in rice endosperm requires the presence of either starch synthase I or IIIa - Fujita, Naoko (Journal of experimental botany, 2011)
Starch synthase (SS) I and IIIa are the first and second largest components of total soluble SS activity, respectively, in developing japonica rice (Oryza sativa L.) endosperm. To elucidate the distinct and overlapping functions of these enzymes, double mutants were created by crossing the ss1 null mutant with the ss3a null mutant. In the F(2) generation, two opaque seed types were found to have either the ss1ss1/SS3ass3a or the SS1ss1/ss3ass3a genotype. Phenotypic analyses revealed lower SS activity in the endosperm of these lines than in those of the parent mutant lines since these seeds had different copies of SSI and SSIIIa genes in a heterozygous state. The endosperm of the two types of opaque seeds contained the unique starch with modified fine structure, round-shaped starch granules, high amylose content, and specific physicochemical properties. The seed weight was ∼90% of that of the wild type. The amount of granule-bound starch synthase I (GBSSI) and the activity of ADP-glucose pyrophosphorylase (AGPase) were higher than in the wild type and parent mutant lines. The double-recessive homozygous mutant prepared from both ss1 and ss3a null mutants was considered sterile, while the mutant produced by the leaky ss1 mutant×ss3a null mutant cross was fertile. This present study strongly suggests that at least SSI or SSIIIa is required for starch biosynthesis in rice endosperm